The digital future of museums conversations and provocations - Winesmith, Keir; Anderson, Susan (Susan Jane) (Abingdon, Oxon Routledge, 2020)
"The Digital Future of Museums: Provocations and Conversations argues that museums today can neither ignore the importance of digital technologies when engaging their communities, nor fail to address the broader social, economic, and cultural changes that shape their digital offerings. Through moderated conversations with respected and influential museum practitioners, thinkers and experts in related fields, this book explores the role of digital technology in contemporary museum practice within Europe, the USA, Australasia and Asia. It offers provocations and reflections about effective practice that will help prepare today's museums for tomorrow, culminating in a set of competing possible visions for the future of the museum sector. The Digital Future of Museums is essential reading for museum studies students and those who teach or write about the museum sector. It will also be of interest to those who work in, for, and with museums, as well as practitioners working in galleries, archives and libraries"--Provided by publisher.
Introduction -- Some Provocations on the Digital Future of Museums -- Conversations on the Digital Future of Museums -- Conversation #1: Seph Rodney + Robert J. Stein -- Conversation #2: LaToya Devezin + Barbara Makuati-Afitu -- Conversation #3: Lara Day + David Smith -- Conversation #4: Sarah Brin + Adriel Luis -- Conversation #5: Sarah Kenderdine + Merete Sanderhoff -- Conversation #6: Kati Price + Loic Tallon -- Conversation #7: Shelley Bernstein + Seb Chan -- Conversation #8: Kate Livingston + Andrew McIntyre -- Conversation #9: Brad Dunn + Daryl Karp -- Conversation #10: Arthur Cohen + Tonya Nelson -- Conversation #11: Tony Butler + Lori Fogarty -- Conversation #12: Daniel Glaser + Takashi Kudo -- Digital Practice in Museums: Where do we go from here?
Includes bibliographical references (pages [225]-232) and index.
Keywords: Museums -- Technological innovations; Museums -- Information technology; Digital media; Museums -- Social aspects; Virtual museums; Cultural property -- Digitization